2012
DOI: 10.3390/jrfm5010059
|View full text |Cite
|
Sign up to set email alerts
|

The Behaviour of Small Investors in the Hong Kong Derivatives Markets: A Factor Analysis

Abstract: This paper investigates the behaviour of small investors in Hong Kong’s derivatives markets. The study period covers the global economic crisis of 2011- 2012, and we focus on small investors’ behaviour during and after the crisis. We attempt to identify and analyse the key factors that capture their behaviour in derivatives markets in Hong Kong. The data were collected from 524 respondents via a questionnaire survey. Exploratory factor analysis was employed to analyse the data, and some interesting findings we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 18 publications
0
9
0
1
Order By: Relevance
“…Lim (2012), Bakar and Yi (2016) find that investors' decisions are significantly affected by overconfidence. Moreover, Hon (2012) concluded that small investors in the Hong Kong Stock Market were overconfident. Longjie and Anfeng (2017) find a positive correlation between overconfidence and investment level in the Chinese Stock Market.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Lim (2012), Bakar and Yi (2016) find that investors' decisions are significantly affected by overconfidence. Moreover, Hon (2012) concluded that small investors in the Hong Kong Stock Market were overconfident. Longjie and Anfeng (2017) find a positive correlation between overconfidence and investment level in the Chinese Stock Market.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Moreover, herd behaviour has been found in numerous stock markets around the world, including advanced and Asian stock markets (Chiang and Zheng, 2010). Hon (2012) found that small investors in the Hong Kong Stock Market follow herd behaviour. Choi and Skiba (2015) find herd behaviour in 41 stock markets around the world.…”
Section: 2mentioning
confidence: 99%
“…Such factors can become a major block or motive for their decision to trade with derivatives. These factors are identified by observing the study result of Hon (2012). Using factor analysis, he identified five factors that capture the behaviour of small investors in derivatives markets in Hong Kong.…”
Section: Behavioral Factorsmentioning
confidence: 99%
“…As a result, anomalies were formed in the market. Hon (2012), in his work, investigated the behavior of small investors operating in derivative markets in Hong Kong. The time period of the study is between 2011-2012.…”
Section: Literature Reviewmentioning
confidence: 99%